The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1753-0407.12964
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin associates with poor β‐cell function, glucose‐dependent insulinotropic peptide, and insulin resistance in persistent type 2 diabetes after Roux‐en‐Y gastric bypass in humans

Abstract: Background: The determinants of type 2 diabetes (T2D) remission and/or relapse after gastric bypass (RYGB) remain fully unknown. This study characterized β-and α-cell function, in cretin hormone release and insulin sensitivity in individuals with (remitters) or without (non-remitters) diabetes remission after RYGB. Methods: This is a cross-sectional study of two distinct cohorts of individuals with or without diabetes remission at least 2 years after RYGB. Each individual under-wenteither an oral glucose (remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For some individuals, reductions in metabolic demand may enable reversal of beta-cell dysfunction, as illustrated by improvements in proinsulin levels and proinsulin/insulin ratios. For example, T2D subjects who respond to bariatric surgery with diabetes remission are characterized by lower proinsulin levels and proinsulin/C-peptide ratios than nonremitters ( 20 ). In contrast, increased metabolic demand with experimental induction of insulin resistance and increased insulin secretion can increase proinsulin/insulin ratios in T2D subjects ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For some individuals, reductions in metabolic demand may enable reversal of beta-cell dysfunction, as illustrated by improvements in proinsulin levels and proinsulin/insulin ratios. For example, T2D subjects who respond to bariatric surgery with diabetes remission are characterized by lower proinsulin levels and proinsulin/C-peptide ratios than nonremitters ( 20 ). In contrast, increased metabolic demand with experimental induction of insulin resistance and increased insulin secretion can increase proinsulin/insulin ratios in T2D subjects ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like SG, the outcomes of RYGB published in relevant trials have shown a progressive worsening of diabetes-related parameters such as glycated hemoglobin, reaching a 50% relapse in diabetes at five years [ 2 ]. Patel et al proposed weak beta-cell function and peripheral insulin resistance as possible causes of relapse after RYGB [ 43 ]. An decrease in beta-cell mass and an increase in alpha-cell mass could explain this, but what is the mechanism that triggers trans-differentiation?…”
Section: Discussionmentioning
confidence: 99%
“…The incretin hormone glucagon‐like peptide‐1 (GLP‐1), secreted in response to nutrient ingestion, is critical for postprandial glucose‐mediated insulin secretion 3 . After RYGB, postprandial circulating GLP‐1 concentrations increase 5‐10‐fold in response to accelerated nutrient entry and absorption 4 and the blunted incretin effect observed in T2D 5 is restored; these effects occur within days 4,6 and persist for years 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…3 After RYGB, postprandial circulating GLP-1 concentrations increase 5-10-fold in response to accelerated nutrient entry and absorption 4 and the blunted incretin effect observed in T2D 5 is restored; these effects occur within days 4,6 and persist for years. 7,8 The contribution of endogenous GLP-1 to improved β-cell function and glycaemia after RYGB has been investigated by blocking the GLP-1 receptor with the peptide exendin 9À39 (EX9) during a mixed meal or oral glucose administration. Intravenous infusion of EX9 before an oral stimulus blunts insulin secretion by approximately half and reverses the improvement in β-cell glucose sensitivity (BCGS) observed after RYGB.…”
mentioning
confidence: 99%